APPLICATION OF BUSINESS MODEL CANVAS (BMC) IN THE DEVELOPMENT OF HOME INDUSTRY RIKA BAKERY DESAMARYKE, KUTAMBARU DISTRICT, LANGKAT REGENCY - Rasykah Fakhirah Balqis; Suryadi Suryadi; Irada Sinta (Jurnal Mahasiswa Agribisnis, 2025)
Home industry Rika Bakery is a company engaged in the processing of flour raw materials into products. It was established in 2020 and is based in Maryke Village, Kutambaru District, Langkat Regency. Product sales are still subject to fluctuations because the products are not durable, a clear accounting system is not implemented, and the business strategy for business development is not clear. These are obstacles that homeowners face. This research aims to determine the application of Business Model Canvas (BMC) in the development of Rika Bakery cottage industry in Maryke Village, Kutambaru District, Langkat Regency. This research uses a qualitative research approach using the Business Model Canvas (BMC) as the data analysis method. The results of this research show that the Rika Bakery home industry has implemented the Canvas business model, but it is not optimal because there are segments in the existing key partnership block that use important resources as their own resources and whose main activity is the creation of product value, utilization of fixed costs and variable costs in carrying out business activities, in the value proposition block, lack of diversity to strengthen the value offered to consumers, use of only one marketing channel, namely direct, use of customer relationships as a form of consumer loyalty, potential present to consumers in product sales to generate revenue only from the achieved product sales.